2003
DOI: 10.1159/000071946
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Binding in the Human Umbilical Cord from Normally Grown Pregnancies and from Pregnancies Complicated by Intra-Uterine Growth Retardation with Absent or Reversed Diastolic Flow

Abstract: The content and the distribution of the glycoconjugate sugar residues were investigated in the human umbilical cord from normally grown pregnancies and from pregnancies complicated by intra-uterine growth retardation with absent or reversed flow in the umbilical artery. The gestational age range was 29–41 weeks. For this purpose, a battery of eight horseradish peroxidase conjugated lectins was used (ConA, WGA, PNA, SBA, DBA, LTA, UEA I, and OOA; see text). Our data showed that in both study groups ConA, WGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…3)-N-acetyl-D-galactosamine and a-Lfucose (LTA and UEA I) were more abundant in the peripheral portion of the jelly with respect to the adventitial one in according to the data observed in a previous study [7]. Even in the groups 2 and 3 N-acetyl-D-glucosamine, D-galactose-(b1 !…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…3)-N-acetyl-D-galactosamine and a-Lfucose (LTA and UEA I) were more abundant in the peripheral portion of the jelly with respect to the adventitial one in according to the data observed in a previous study [7]. Even in the groups 2 and 3 N-acetyl-D-glucosamine, D-galactose-(b1 !…”
Section: Discussionsupporting
confidence: 74%
“…3)-N-acetyl-D-galactosamine and a-Lfucose (UEA I) had the same distribution in the two portions; in the group 3 also sialic acid showed this distribution, while in the group 2 it was present only in the adventitial portion. As suggested by a previous study [7], the different amount of carbohydrates in the two portions might contribute to exert their different functions: protection of the vessels by the peripheral portion and diffusion of substances between the vessels by the adventitial one. In the pathological groups, in particular in the minor degree of glucose intolerance, the lacking of some carbohydrates in both the portions might contribute to impair their functions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Importantly, this conclusion is also supported from studies comparing patterns of lectin binding in human tissues under healthy and diseased states. Examination of lectin binding to umbilical cords demonstrated increased ConA and UEA binding to the vein compared with the artery and lectinbinding patterns during pregnancy complications are altered in both pattern and intensity within the vasculature (Sgambati et al 2003(Sgambati et al , 2007. Our own studies have shown that there Scott et al (2012).…”
Section: Lectin-binding Patterns Vary Between Vascular Bedsmentioning
confidence: 67%